Self-assembly of diblock copolymer in bulk and solution - Pan, Hongwei; Wu, Min; He, Linli (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2014)
The dissipative particle dynamics (DPD) simulation method are used to study the self-assembly of diblock copolymer (A(m)B(n)) in melts and in selective solutions. For bulk case, the phase behaviors of cyclic and linear diblock copolymer are compared systematically. The order-disorder transition and the period size of a special phase are observed. In the case of B selective solution varying in the chain length of cyclic diblock copolymer, some diverse morphologies are observed, such as sphere, discoid, sheet, hollow cylinder and hollow sphere.